Connecting wires and accessories to the micro:bit : getting started with an ARM-based embedded system - Underwood, Lorraine (Apress, 2018)
"Learn multiple ways to connect different types of wires to the micro:bit. This video shows you how to use items found in a typical hardware store, therefore making all its methods accessible to the average person. There is no soldering involved. In this video, you will cover the advantages and disadvantages of each method, as well as see code samples that demonstrate how data is transferred from different accessories to the micro:bit. The micro:bit edge connector gives you access to five pins: three input and output pins and two pins for powering other devices. This allows you to add lots of extra accessories such as buttons, lights and motors to the micro:bit. There are many edge connector breakout boards available for adding accessories to the micro:bit available commercially at an extra cost."--Resource description page